Aloes: a journey from traditional herb to modern panacea - Sudesh Kumar Banyal; Lal Bahadur
Aloe vera, the most popular member of the genus Aloe L., is a wonderful healing plant that has been used for the last 6000 years since ancient Egyptian times for its wide of range of pharmaceutical and nutraceutical applications. However, most of the available literature emphasizes on the properties of this one species only. Most probably, due to its early introduction to the world, it becomes dominant in the use, even though several other species also have great therapeutic potential. Emphasizing the broader significance of Aloe species beyond Aloevera is crucial for unlocking their diverse applications. Aloe arborescens, Aloe ferox, and Aloe excelsa showcase potent antimicrobial properties, contributing significantly to skincare. Aloe secundiflora addresses kidney problems, while Aloe deserti and Aloe secundiflora find traditional use against malaria. Recent scientific studies underscore Aloe vera's potential in dentistry, diabetes management, anti-inflammatory actions, and anti-cancer effects. Species such as Aloe claviflora and Aloe littoralis reveal impressive antioxidant capabilities. Aloe vera and Aloe ferox lead in cosmetics, with their unique properties. Aloe trinervis leaves are consumed as food. Additionally, Aloevera waste proves beneficial in environmental management, particularly in phytoremediation for arsenic toxicity. Caution is crucial due to their potential toxicity, emphasizing the need for careful application. Exploring the diverse Aloe genus is imperative for comprehending their specific applications and unlocking untapped industrial potential, promising a wealth of possibilities for various fields.